2023
DOI: 10.3390/cancers15082321
|View full text |Cite
|
Sign up to set email alerts
|

P2X1 and P2X7 Receptor Overexpression Is a Negative Predictor of Survival in Muscle-Invasive Bladder Cancer

Abstract: Bladder cancer is amongst the most common causes of cancer death worldwide. Muscle-invasive bladder cancer (MIBC) bears a particularly poor prognosis. Overexpression of purinergic P2X receptors (P2XRs) has been associated with worse outcome in several malignant tumors. Here, we investigated the role of P2XRs in bladder cancer cell proliferation in vitro and the prognostic value of P2XR expression in MIBC patients. Cell culture experiments with T24, RT4, and non-transformed TRT-HU-1 cells revealed a link betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…High P2X7R expression was correlated with decreased overall survival in a cohort of patients with lung adenocarcinoma from The Cancer Genome Atlas (TCGA) dataset (92). In muscle-invasive bladder cancer, P2X7R has been reported as a negative predictor of overall survival (93). These findings have been validated through TCGA analysis (94).…”
Section: Prognostic Value Of P2x7r Expression In Cancermentioning
confidence: 87%
“…High P2X7R expression was correlated with decreased overall survival in a cohort of patients with lung adenocarcinoma from The Cancer Genome Atlas (TCGA) dataset (92). In muscle-invasive bladder cancer, P2X7R has been reported as a negative predictor of overall survival (93). These findings have been validated through TCGA analysis (94).…”
Section: Prognostic Value Of P2x7r Expression In Cancermentioning
confidence: 87%
“…EMT is a process of cell transdifferentiation originally adopted during embryogenesis and co-opted during metastasis, causing an increase in cancer cell migration linked to loss of cell polarity and down-regulation of adhesion molecules [99]. This mechanism was confirmed as the basis of P2X7-mediated invasiveness in recent publications covering the negative prognostic role of the receptor in oncological conditions as different as neuroblastoma [44], triple-negative breast cancer [100] and muscle-invasive bladder carcinoma [101]. In addition to EMT, metastasis is favored by signaling pathways and mechanisms implicated in tissue regeneration, wound healing, and adaptation to stress [90] that have been associated with P2X7 activity both in cancer and other physio-pathological conditions [17,53,55,84,96,[102][103][104][105][106][107][108].…”
Section: P2x7 and Metastasismentioning
confidence: 93%
“…Finally, P2X7 promotes autophagy [ 17 , 44 , 106 , 107 , 108 ] and unfolded protein responses [ 113 ], which help confer metabolic and immune evasive plasticity in solid cancers [ 90 ]. Given the involvement of the P2X7 receptor in the aforementioned metastasis-promoting signaling pathways and mechanisms, it is not surprising that overexpression of the receptor was associated with metastatic stages of multiple cancers [ 43 , 55 , 101 , 114 , 115 , 116 , 117 , 118 ]. Accordingly, P2X7 antagonism proved efficacious in reducing the in vivo dissemination of cancer cells in animal models of metastasis [ 41 , 43 , 78 , 91 , 92 , 96 , 119 ].…”
Section: P2x7 and Metastasismentioning
confidence: 99%
“…However, some findings have shown that overexpression of the P2RX1 gene is strongly associated with disease progression and shorter survival time in urological malignant bladder cancer. The P2RX1 gene's high expression increases the risk of distant metastasis of bladder cancer cells [50].…”
Section: Agingmentioning
confidence: 99%